Visibility of the mandibular canal on CBCT crosssectional images - Christiano Oliveira-Santos; Ana Lúcia Álvares Capelozza; Mariela Siqueira Gião Dezzoti; Cássia Maria Fischer; Marcelo Lupion Poleti; Izabel Regina Fischer Rubira-Bullen (University of São Paulo, 2011)
The identification of the mandibular canal (MC) is an important prerequisite for surgical procedures involving the posterior mandible. Cone beam computed tomography (CBCT) represents an advance in imaging technology, but distinguishing the MC from surrounding structures may remain a delicate task. OBJECTIVES: The aim of this study was to assess the visibility of the MC in different regions on CBCT cross-sectional images. MATERIAL AND METHODS: CBCT cross-sectional images of 58 patients (116 hemi-mandibles) were analyzed, and the visibility of the MC in different regions was assessed. RESULTS: The MC was clearly visible in 53% of the hemi-mandibles. Difficult and very difficult visualizations were registered in 25% and 22% of the hemi-mandibles, respectively. The visibility of the MC on distal regions was superior when compared to regions closer to the mental foramen. No differences were found between edentulous and tooth-bearing areas. CONCLUSIONS: The MC presents an overall satisfactory visibility on CBCT cross-sectional images in most cases. However, the discrimination of the canal from its surrounds becomes less obvious towards the mental foramen region when cross-sectional images are individually analyzed.